Exchange rate pass-through in Turkish export and import prices - TEKİN, RIFAT BARIŞ (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2009)
This article examines exchange rate pass-through into prices of internationally traded goods in the case of a small emerging open market economy such as Turkey. In this study, we provide empirical evidence on complete pass-through in export prices in Turkey using aggregate data on the manufacturing sector. Our data do not however support complete pass-through in import prices in Turkey. This contradicts with the findings of the existent literature, which typically concludes that the degree of pass-through in import prices is higher than the one of export prices. This can be interpreted as a result of competition between import and import substituting industries where importers fall short of competing successfully with import substituting sectors. Although Turkish importers can be responsive to exchange rate changes to a certain degree in the short-run, in the long-run, they seem to lose their market power perhaps as a result of swift competition. A complete exchange rate pass-through to export prices in Turkey implies that the Turkish manufacturing export sector has the competitive strength to transmit exchange rate movements into their prices.
Keywords: UNIT-ROOT; COINTEGRATION; TESTS; ECONOMY